Epstein-Barr virus infection and gastric carcinoma in São Paulo State, Brazil - Lopes,L.F. (2004)
Epstein-Barr virus (EBV) is a ubiquitous herpesvirus, and most people have serological evidence of previous viral infection at adult age. EBV is associated with infectious mononucleosis and human cancers, including some lymphomas and gastric carcinomas. Although EBV was first reported in lymphoepithelioma-like gastric carcinoma, the virus was also found in conventional adenocarcinomas. In the present study, 53 gastric carcinomas diagnosed in São Paulo State, Brazil, were evaluated for EBV infection by non-isotopic in situ hybridization with a biotinylated probe (Biotin-AGACACCGTCCTCACCACCC GGGACTTGTA) directed to the viral transcript EBER-I, which is actively expressed in EBV latently infected cells. EBV infection was found in 6 of 53 (11.32%) gastric carcinomas, mostly from male patients (66.7%), with a mean age of 59 years old. Most EBV-positive tumors were in gastric antrum. Two EBV-positive tumors (33.3%) were conventional adenocarcinomas, whereas four (66.7%) were classified as lymphoepithelioma-like carcinomas. EBV infection in gastric carcinomas was reported elsewhere in frequencies that range from 5.6% (Korea) up to 18% (Germany). In Brazil, a previous work found EBV infection in 4 of 80 (5%) gastric carcinomas, whereas another study found 4.7 and 11.2% of EBV-positive gastric carcinomas of Brazilians of Japanese origin or not, respectively. In the present study, the frequency of EBV-positive gastric carcinomas is similar to that reported in other series, and the clinicopathologic characteristics of these EBV-positive tumors are in agreement with the data in the literature.